'A more inclusive mind towards the world': English language teaching and study abroad in China from intercultural citizenship and English as a lingua franca perspectives. (September 2018) - Fang, Fan (Gabriel); Baker, Will
With the status of English as a global lingua franca (ELF), English is no longer the sole property of its Anglophone native English speakers (NES) problematizing the current dominance of Anglophone cultures and NES in the field of English language teaching (ELT). The notion of intercultural citizenship education offers a critical alternative model in language education. To investigate how ELF, intercultural approaches and the concept of intercultural citizenship might be integrated within the field of ELT, a study was conducted in a university located in southeast China. Due to the large number of ELT learners and high degree of student mobility in China these are issues of much relevance in this setting. The research collected qualitative data through face-to-face interviews, email interviews and focus groups with students on study abroad programmes who have both ELT and first-hand intercultural experiences. Many students spoke positively about aspects of intercultural citizenship, but classroom instruction offered only limited channels for students to experience and understand intercultural communication and citizenship. In contrast, most of their understanding and experiences were gained outside the classroom during study abroad. Furthermore, many students spoke about the importance of English in their development of intercultural connections and citizenship. We conclude that more in-depth and critical approaches to teaching language, culture and intercultural communication in ELT are needed which foster and cultivate students' sense of intercultural citizenship.